2018
DOI: 10.18203/2320-6012.ijrms20180291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clonidine and fentanyl as an adjuvant to bupivacaine in unilateral spinal anaesthesia

Abstract: Background: Various adjuvants to local anaesthetics are added to improve the quality of subarachnoid block in unilateral anaesthesia during lower limb surgeries. The present study was conducted with the aim to evaluate the efficacy of combination of clonidine-bupivacaine and fentanyl-bupivacaine.Methods: This randomized study was conducted on 60 patients at tertiary care center (Topiwala National Medical College, Mumbai) for 2 years. They were divided into 2 groups consisting of 30 in each. Group BC receives I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…9,11,16 Thus, there were no episodes of hypotension or bradycardia in both groups. This observation was seen in spite of not pre-loading patients with intravenous fluids prior to administration of unilateral spinal anaesthesia as was done in studies by Khadse PB et al, 17 and Singh T K et al 18 We didn't use control group in our study as previous studies have demonstrated that nalbuphine and fentanyl prolonged duration of sensory block and analgesia. 14,[17][18][19] We were able to achieve unilateral in 85% of our enrolled patients, this might be due to variation in height, weight, rate of drug administration in these patients.…”
Section: Comparing 08 Mg Nalbuphine As Adjuvant With 20 µG Fentanyl I...mentioning
confidence: 76%
“…9,11,16 Thus, there were no episodes of hypotension or bradycardia in both groups. This observation was seen in spite of not pre-loading patients with intravenous fluids prior to administration of unilateral spinal anaesthesia as was done in studies by Khadse PB et al, 17 and Singh T K et al 18 We didn't use control group in our study as previous studies have demonstrated that nalbuphine and fentanyl prolonged duration of sensory block and analgesia. 14,[17][18][19] We were able to achieve unilateral in 85% of our enrolled patients, this might be due to variation in height, weight, rate of drug administration in these patients.…”
Section: Comparing 08 Mg Nalbuphine As Adjuvant With 20 µG Fentanyl I...mentioning
confidence: 76%